Correlation Between Intraocular Pressure and Central Corneal Thickness in Persian Children. Issue 2 (December 2016) - Nejabat, Mahmood; Heidary, Fatemeh; Talebnejad, Mohammad; Salouti, Ramin; Nowroozzadeh, Mohammad; Masoumpour, Masoumeh; Mahdaviazad, Hamideh; Tajbakhsh, Zahra; Keshtkar, Maryam; Jamali, Hossein; Khalili, Mohammad; Movahedan, Hossein; et al.
Abstract Introduction This study aimed to determine intraocular pressure (IOP) and central corneal thickness (CCT) measurements in healthy Persian children to find clinical reference values in this ethnicity. Additionally, we examined the possible relationship between these measurements. Methods This cross-sectional study included 262 eyes of 131 Persian primary school children between 6 and 13 years of age. All eyes were healthy and had no anterior or posterior segment abnormalities, corneal disease, or evidence of glaucoma. Specular microscopy was used to measure CCT and both noncontact tonometry (NCT) and Goldmann applanation tonometer (GAT) were used to measure IOP. Correlations between IOP measurements were also examined. Results Mean CCT was 513.47 ± 34.51 μm in the right eye (OD) and 513.93 ± 33.88 μm in the left eye (OS). The CCT was not significantly different between older (10–13 years) and younger (6–9 years) patients. Mean IOP measured with GAT was 13.86 ± 2.13 mmHg OD and 13.72 ± 2.04 mmHg OS and mean IOP measured with NCT was 15.26 ± 2.38 mmHg OD and 15.11 ± 2.18 mmHg OS. The IOP and CCT measured with GAT were weakly correlated (OD:r = 0.141, P = 0.114; OS:r = 0.236, P = 0.007). However, IOP and CCT measured with NCT (OD:r = 0.487, P = 0.000; OS:r = 0.456, P = 0.000) were moderately correlated. Our outcomes demonstrated that for 100 μm increase in CCT, IOP measured with GAT and NCT increased by 0.8 and 3.3 mmHg, respectively, in OD and by 1.4 and 2.9 mmHg in OS. Based on intraclass correlation coefficients, IOP measurements made with GAT and NCT were in fair agreement in OD and in good agreement in OS. Conclusion The IOP and CCT in healthy Persian school children (6–13 years old) were positively correlated. Our findings revealed that corneal thickness is thinner in Persian children than in most other racial groups. Funding This study has been funded by deputy dean in research of School of Medicine and deputy vice chancellor of Shiraz University of Medical Sciences, Shiraz, Iran.